The Use of Expressions in Improving Kalam Skill in Learning Arabic for MTSN 2 Kediri Students - Jauharoh, Ervin; Anam, Wahidul; Huda, Mokhammad Miftakhul (Asalibuna, 2021)
The purposes of this study were to find out the usage of expressions for improving speaking skill in teaching Arabic for students in the Islamic Junior High School 2 Kediri, and to know the effectiveness of it. The approach used for this research was a quantitative approach. As for the research method, it was the experimental method. The population in this research was the students in the Islamic Junior High School 2 Kediri in the 8th grade "A" with a total of 35 students. Then the researcher divided into two groups, namely the control group and the experimental group. The number of students in the control group was fifteen and twenty students were in the experimental group. The results of this research was T = 14,600 and sig (p) = 0,000, 0,505. H0 = Payback and H1 = Acceptable. So there was a difference between using expressions before and after. In other words, the application of expressions for improving speaking skill is useful for facilitating daily communication between students.